Accuracy of single crowns fabricated from ultrasound digital impressions. Issue 11 (November 2018) - Praça, Luciano; Pekam, Fabrice Chuembou; Rego, Rodrigo Otavio; Radermacher, Klaus; Wolfart, Stefan; Marotti, Juliana
Highlights: Ultrasound scanner can make dental digital impressions under porcine gingiva. Ultrasound scanner crowns presented mean marginal gap of 117.59 ± 55.86 μm. Ultrasound scanner crowns presented lower marginal fit compared to optical ones. Ultrasound crowns presented internal fit similar to at least one optical scanner. Abstract: Objective: This in vitro study aimed to evaluate marginal and internal fit of single crowns produced from high-frequency ultrasound based digital impressions of teeth prepared with finish lines covered by porcine gingiva, in comparison with those obtained by optical scanners with uncovered finish lines. Methods: Ten human teeth were prepared and forty zirconia crowns were fabricated from STL-datasets obtained from four dental scanners (n = 10): extraoral CS2 (Straumann), intraoral Lava COS (3M), intraoral Trios (3Shape) and extraoral ultrasound scanner. The accuracy of the crowns was compared evaluating marginal and internal fit by means of the replica technique with measurements in four areas; P1: occlusal surface; P2: transition between occlusal and axial surfaces; P3: middle of axial wall; and P4: marginal gap. Restoration margins were classified according to their mismatch as regular, underextended or overextended. Kruskal–Wallis one-way ANOVA and Mann–Whitney U test were used to evaluate the differences between groups at p < 0.05. Results: The median value of marginal gap (P4) for Ultrasound (113.87 μm) differed statistically from that of CS2 (39.74 μm), Lava COS (41.98 μm) and Trios (42.07 μm). There were no statistical differences between ultrasound and Lava COS for internal misfit (P1–P3), however there were statistical differences when compared with the other two scanners (Trios and CS2) at P1 and P2. Significance: The ultrasound scanner was able to make digital impressions of prepared teeth through porcine gingiva (P4), however with less accuracy of fit than that of conventional optical scanners without coverage of the finish lines. Where no gingiva was available (P1–P3), the ultrasound accuracy of fit was similar to that of at least one optical scanner (Lava COS).